A pretreatment prognostic score to stratify survival in pancreatic cancer - Hank, Thomas; Hinz, Ulf; Reiner, Thomas; Malleo, Giuseppe; König, Anna-Katharina; Maggino, Laura; Marchegiani, Giovanni; Kaiser, Jörg; Paiella, Salvatore; Binco, Alessandra; Salvia, Roberto; Hackert, Thilo; et al. (Annals of surgery, 2022)
The aim of this study was to develop and validate a pretreatment prognostic score in pancreatic cancer (PDAC). Pretreatment prognostication in PDAC is important for treatment decisions but remains challenging. Available prognostic tools are derived from selected cohorts of patients who underwent resection, excluding up to 20% of patients with exploration only, and do not adequately reflect the pretreatment scenario.